2009
DOI: 10.1002/pssc.200982525
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric spectroscopy of CuBiP2S6 crystals

Abstract: Investigation results of broadband dielectric (20 Hz–1 MHz) properties of layered CuBiP2S6 crystals are presented. At higher temperatures the dielectric properties are strongly influenced by high electrical conductivity. The DC conductivity and conductivity relaxation time exhibit an anomaly close to the phase transition temperature Tc=220 K. Activation energies of both parameters are very similar, this suggests that the conductivity mechanism is single Cu ions hopping, and phase transition is of superionic ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…As lowering T, the data fit well near room T but start to deviate below 250 K. The fitting is extended to the lower T to show the broad slope change ≈230 K. The estimated activation energy of ≈0.61 eV near room T is similar to the value of CIPS in the paraelectric (PE) state, indicating that a significant interlayer hopping of the Cu 1+ ion occurs above 250 K, which is the on-set of the ionic conductivity. [9,26,27] Upon further cooling, σ(T) shows a broad peak at ≈50 K and becomes flattened below 30 K. Note that the magnetic susceptibility observed in a previous study showed a deviation from a paramagnetic behavior at ≈50 K, and the following antiferromagnetic long-range ordering at T N = 32 K. [18] These anomalies in σ(T) are consistent with the appearance of the magnetic ordering of CCPS, implying a possible magneto-dielectric correlation.…”
Section: Ferroelectricity In Antiferroelectric Cucrp 2 Ssupporting
confidence: 60%
“…As lowering T, the data fit well near room T but start to deviate below 250 K. The fitting is extended to the lower T to show the broad slope change ≈230 K. The estimated activation energy of ≈0.61 eV near room T is similar to the value of CIPS in the paraelectric (PE) state, indicating that a significant interlayer hopping of the Cu 1+ ion occurs above 250 K, which is the on-set of the ionic conductivity. [9,26,27] Upon further cooling, σ(T) shows a broad peak at ≈50 K and becomes flattened below 30 K. Note that the magnetic susceptibility observed in a previous study showed a deviation from a paramagnetic behavior at ≈50 K, and the following antiferromagnetic long-range ordering at T N = 32 K. [18] These anomalies in σ(T) are consistent with the appearance of the magnetic ordering of CCPS, implying a possible magneto-dielectric correlation.…”
Section: Ferroelectricity In Antiferroelectric Cucrp 2 Ssupporting
confidence: 60%